A Case of Successful Adjustment : Korea's Experience During 1980-84 - Marquez-Ruarte, Jorge (Occasional Papers; Occasional Paper, 1985)
This paper was prepared by Bijan B. Aghevli, Division Chief in the international Monetary Fund's Asian Department, and Jorge Marquez-Ruarte, Senior Economist in the Asian Department. In preparing the paper, the authors have relied extensively on the analysis and information provided by the Korean authorities as well as on the work of the Fund staff on Korea during the period under study.